Innovative Therapies: A Major Breakthrough in Combating Multi-Drugresistant Bacterial Infections Using Mixture Design and Multi-Objective Optimization with NSGA-II Algorithm - Adouane, Meriem; Kadri, Nabil; Benzitoune, Nourelimane; Lakhdari, Chafika; Djellal, Samia; Ousmer, Lilla; Tahraoui, Hichem; Amrane, Abdeltif; Remini, Hocine; Dahmoune, Farid; Madani, Khodir (Current topics in medicinal chemistry, 2025)
The increasing resistance of pathogens to antibiotics poses a major public health challenge. This study aims to develop an innovative approach to combat this resistance by exploring synergies between standard antibiotics and marine metabolites. The methodology combines disk diffusion testing and mixture design to assess the antimicrobial efficacy of the combinations. The results demonstrate promising synergies between carotenoids, polyphenols, and alkaloids with standard antibiotics, offering potential targeted use in the fight against clinical multidrug- resistant bacteria. Specifically, Gram-negative bacteria (BGN) showed increased resistance to antibiotics such as amoxicillin-clavulanic acid (AMC), ceftazidime, cefotaxime, tetracycline, and cefazolin. These antibiotics, when combined with marine compounds, exhibited substantial inhibitory effects against specific isolates, circumventing antibiotic resistance mechanisms. Similarly, substantial synergies were observed in Gram-positive bacteria. Leveraging advanced algorithms such as multi-objective optimization, notably the NSGA-II algorithm, we accurately predicted minimum inhibitory concentrations (MICs) against clinically resistant bacterial isolates. Optimal conditions against Escherichia coli, characterized by carotenoids = 0.6335, total polyphenols = 0, indole alkaloids = 0.1723, and AMC = 0.1941, yielded a predicted MIC of 41.1126 mg/L, closely mirroring the experimental MIC of 41.66 ± 0.18 mg/L. Similarly, for Staphylococcus aureus, optimal conditions produced a predicted MIC of 30.8304 mg/L, closely aligning with the experimental MIC of 30.69 ± 1.80 mg/L. The consistent and reliable predictions for bacterial strains affirmed the robustness of the applied methodology. These results not only pave the way for further exploration but also offer valuable insights for optimizing pharmaceutical and medical interventions, presenting innovative avenues for combating antibiotic-resistant bacterial infections.